Desenvolvimento económico e instituições em Moçambique: Factores que afectam a gestão das finanças públicas - Cruz, António S.; Mafambissa, Fausto J. (2020)
Moçambique alcançou um desenvolvimento socioeconómico incipiente mas ainda frágil, desde 1975. Apesar de o sistema de gestão das finanças públicas ter sido reformado e melhorado, o seu desempenho tem vindo a enfraquecer desde 2013. Utilizando uma abordagem económica institucional, identificámos a estratégia de crescimento económico, o princípio da separação de poderes e o grau de descentralização como factores-chave que afectam o sistema de gestão das finanças públicas. Como a actual estratégia baseada nos recursos naturais parece estar a falhar, sugerimos uma estratégia alternativa de crescimento balanceado no contexto de um sistema político democrático efectivo. Isso implicaria a identificação de políticas prioritárias necessárias para promover um desenvolvimento sustentável e inclusivo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

Economic development and institutions in Mozambique: Factors affecting public financial management - Cruz, António S.; Mafambissa, Fausto J. (2020)
Abstract: Mozambique has achieved incipient but still fragile socio-economic development since 1975. The public financial management system has been reformed and improved, but its performance has weakened since 2013. Applying an institutional economics approach, we have identified the economic growth strategy, the separation of powers principle, and the degree of decentralization as key factors affecting the public financial management system. As the current strategy based on natural resources seems to be failing, we suggest an alternative balanced growth strategy in the context of an effective democratic political system. It would entail the identification of policy priorities required for fostering sustainable and inclusive development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

A Pharmaceutical Logistics still far from answering health concerns of the country: budgetary weaknesses - N'weti (N'weti, 2020)
Key Messages: - Pharmaceutical logistics make up only 7% of total projected costs for the health sector through 2019; - The expansion and demand of the health sector in the forthcoming years will not be accompanied by the necessary increase in resources for the pharmaceutical logistics sector; - Increased nancing in the area of PL is necessary, preferably from internal sources, to allow the implementation of PELF recommendations; - It is estimated that 13% of the value of the approximately $3,929 million needed to procure and manage drugs and commodities during 2014-2019 will be wasted. - The health sector is heavily reliant on external funding, with 81% of funding for medicines comming from external partners; - There is concerning public evidence of systematic stock-outs of medicines in public pharmacies throughout the country. Research by Nweti (2014-2015) in 37 health acilities in four provinces using the community score card as a survey tool, found that stock-out of essential medicines was one of the barriers to accessing quality health services. Another study carried out by Wagenaar, et al. (2014) in Sofala Province, which assessed 26 facilities showed that only one out of the 26 facilities assessed in 2011, 2012, and 2013 had all of the 15 essential medicines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; health / saúde

Uma Logística Farmacêutica ainda distante de responder às preocupações de saúde do país: as fragilidades orçamentais - N'weti (N'weti, 2020)
A área de logística farmacêutica (LF) é vital pelo facto de assegurar que os medicamentos e produtos médicos estejam disponíveis no país e nos pontos de entrega e inclui seleção de medicamentos, quanti cação, procurement, controle de qualidade, armazenamento, transporte e distribuição. O Governo de Moçambique reconhece a importância deste sector e como parte da agenda de reforma do MISAU desenhou o Plano Estratégico de Logística Farmacêutica (PELF) juntamente com o respectivo Plano Operacional (2013). O PELF visa responder a necessidade de providenciar reformas a área de logística farmacêutica melhorando a gestão nanceira, procurement, inventariação, gestão do armazenamento, transporte, distribuição, uso de medicamentos e gestão de recursos humanos. Relatórios disponíveis apontam para a existência de vários desafios na implementação do PELF sendo que a falta de recursos financeiros é um dos maiores desafios para a implementação do quadro de recomendações deste documento. Em Moçambique a LF é actualmente uma das áreas menos favorecidas em termos de dotação orçamental cabendo-lhe 7% do total de envelope de recursos do sector da saúde projectados até 2019 (MISAU/DNPC, 2013). Esta tendência ao ser estacionária ao longo dos próximos 5 anos certamente estará em descompasso com a expansão e aumento da demanda pelos serviços públicos de saúde o que poderá comprometer a prestação do sector de saúde. A actual fonte de nanciamento e práticas de alocação orçamental na área de LF é também problemática. A estimativa da taxa de desperdício de medicamentos e consumíveis representa cerca de 13% do investimento total de $3,929 milhões de dólares da área de Logística Farmacêutica. Uma redução da taxa de desperdício para 5% implicaria numa economia de 332 milhões de dólares durante o PESS 2014 - 2019 (Dutta et al., 2014). Adicionalmente mais de 81% dos fundos para área de medicamentos são nanciados por parceiros externos (Dutta et al., 2014). Esta dependência de fundos externos é preocupante num cenário de incerteza do nanciamento externo ao sector de saúde (Dutta et al., 2014). Os níveis de satisfação da disponibilidade de medicamentos essenciais a nível central apesar de registarem progressos contrastam com a disponibilidade de medicamentos a nível das unidades sanitárias (MISAU, 2013, 2014). Várias Organizações da Sociedade Civil (OSC) incluindo a N ́weti, MSF o CIP tem denunciado sistemáticas rupturas de medicamentos nas unidades sanitárias das províncias do sul, centro e norte do país. Face as rupturas sistemáticas de medicamentos nas unidades sanitárias e a imprevisibilidade do nanciamento externo é crucial que o Governo de Moçambique incremente o volume de nanciamento para a área de LF sobretudo na base de recursos domésticos. A falta de recursos está a afectar grandemente a implementação do PELF e de igual modo a capacidade do sector de saúde em providenciar de forma e ciente serviços de saúde de qualidade.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; health / saúde

Informe Orçamental Acção Social - Mozambique 2020 - UNICEF (UNICEF and Organização Internacional do Trabalho (OIT), 2020)
Principais Mensagens: 1. Apesar do aumento contínuo registado na dotação orçamental destinada à protecção social desde 2010, o nível do espaço fiscal dedicado aos programas de protecção social básica (não contributiva) ainda está aquém das necessidades e, a menos que seja consideravelmente melhorado, é pouco provável que o sistema cumpra a meta estabelecida na ENSSB 2016-2024 (2,23 por cento do PIB). 2. A cobertura específica dos programas de Protecção Social definidos no PQG 2015-2019 não foi cumprida em resultado de dotações sectoriais insuficientes, bem como de ineficiências na execução orçamental. Com o impacto negativo da COVID-19 na renda da população moçambicana, as necessidades de protecção social são maiores do que nunca. Por conseguinte, é ainda mais necessária uma rápida expansão da cobertura, e consequentemente, torna-se necessário proceder a uma dotação orçamental muito maior para 2020 e 2021. 3. O apoio orçamental dos principais doadores (tais como o Banco Mundial e outros) constitui uma importante oportunidade para o sector da Protecção Social cumprir os ambiciosos objectivos de expansão da cobertura. É necessário um mecanismo sólido de monitoria, informação e prestação de contas que garanta o acesso aos recursos, pelo que uma utilização eficaz do e-INAS poderia ser a solução-chave. 4. Embora seja atribuída uma maior dotação orçamental às províncias com maior índice de pobreza / vulnerabilidades, uma grande lacuna ainda está por preencher. No orçamento de 2020, a dotação per capita (por pessoa pobre) nas províncias desfavorecidas do Norte é muito mais baixa do que a das províncias relativamente mais ricas do Sul. Como forma de reduzir a desigualdade, é necessária uma expansão da cobertura, bem como a priorização de áreas com taxas de pobreza mais elevadas.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento